Ophthalmology Resident Oculofacial Surgery Case Exposure: An ACGME Case Log Analysis. Issue 2 (28th October 2022) - Abousy, Mya; Schilling, Andy; Qiu, Mary; Rajaii, Fatemeh; Li, Ximin; Woreta, Fasika A.
Abstract : Purpose: The authors quantified trends in resident oculofacial surgery exposure between 2009 and 2018, reviewed specific procedure volume, and correlated procedure volume with program characteristics. Methods: The authors requested de-identified case logs of residents graduating US ophthalmology residency programs in 2018 from all 118 programs. Current Procedural Terminology codes of all oculofacial procedures were analyzed. Current Procedural Terminology codes were grouped into 25 unique categories that the authors created in addition to the 11 Accreditation Council for Graduate Medical Education categories. Results: One hundred and sixty-six of 488 (34%) US ophthalmology residents graduating in 2018 provided case logs (32.2% of programs). According to Accreditation Council for Graduate Medical Education case logs, residents graduating in 2018 completed significantly fewer eye removal/implant procedures, lacrimal surgeries, "other orbital" procedures, entropion/ectropion repairs, and temporal artery biopsies as primary surgeon than residents graduating in 2009, yet significantly more eyelid laceration repairs, chalazion excisions, tarsorrhaphies, ptosis repairs, and blepharoplasty/reconstruction procedures ( p < 0.05). No difference was found between the total number of oculofacial cases between 2009 and 2018 ( p = 0.051). The most frequently logged procedure per resident in the sample was blepharoplasty/reconstruction (17.2 ± 15) followed by "other oculoplastic" (12.7 ± 10.6). The least commonly performed procedures included temporal artery biopsy (1.5 ± 2.2) and "other orbital" (1.9 ± 3.1). Program size, location, and presence of oculofacial fellowship program all impacted case volume. Conclusions: Oculofacial surgery has the second highest case number requirement for residents per Accreditation Council for Graduate Medical Education guidelines. However, resident exposure to oculofacial surgery cases greatly varies in each ophthalmology residency program. Abstract : US ophthalmology residency programs differ in oculofacial surgery case volume based on program size, presence of oculofacial surgery fellowship program, and location. Furthermore, specific procedure case volume has varied between 2009 and 2018.